Regional simulation of nitrate leaching potential from winter wheat-summer maize rotation croplands on the North China Plain using the NLEAP-GIS model - Li, Zhuoting; Wen, Xiumei; Hu, Chunsheng; Li, Xiaoxin; Li, Shanshan; Zhang, Xiaosen; Hu, Baoqing (Agriculture, ecosystems & environment, 2020)
•Regional simulation of nitrate leaching from NCP croplands was done using NLEAP-GIS.•Spatial-temporal variation of nitrate leaching in North China Plain was quantified.•Water input, fertilizer and soil jointly affect N leaching spatial-temporal pattern.•Optimal fertilizer N rates were recommended for winter wheat-summer maize rotation.•Spatial distribution of potential groundwater nitrate pollution risk was implied. Identifying the regional characteristics of nitrate leaching from croplands is of great importance when attempting to assess the groundwater contamination risk due to nitrate leaching from croplands. The regional scale model in the Nitrogen Loss and Environmental Assessment Package with GIS Capabilities (NLEAP-GIS), which takes spatial variations in soil profile properties, meteorological data, and farm practices into account, was adopted in this study to simulate the occurrence dynamics and spatial pattern of nitrate leaching downwards through the crop root zone (0–100 cm) in winter wheat (Triticum aestivum L.)-summer maize (Zea mays L.) rotation croplands during 2011 and 2012 across the Jing-Jin-Ji region on the North China Plain (NCP). The results showed that the monthly nitrate leaching occurrences were driven by rainfall, irrigation, and fertilizer application. The simulated large spatial variation in cumulative nitrate leaching was positively correlated with both rainfall and fertilizer N application rates, whereas it was negatively correlated with N use efficiency. The cumulative nitrate leaching was mostly lower than 10 kg N ha–1 during the winter wheat growing season, whereas nitrate leaching during the summer maize growing season was much higher and mostly ranged from 20 to 100 kg N ha–1. The average cumulative nitrate leaching in the winter wheat-summer maize rotation system was 55.7 ± 33.5 kg N ha–1, accounting for 17.2 ± 10.2 % of the fertilizer N applied (average 176.3 ± 86.2 kg N ha–1 during each crop season). Fertilizer N application rates of 100–200 kg N ha–1 are recommended during each winter wheat and summer maize season to simultaneously achieve higher grain yields, greater N use efficiency, and a lower groundwater nitrate pollution risk on the NCP. The simulated spatial variation in nitrate leaching implied that there was a potential nitrate groundwater contaminant source and the results contributed to the spatial distribution assessment of groundwater nitrate contamination risk caused by fertilizer N inputs.